Heuweltjies : a window into the palaeoclimate and palaeovegetation of the Western Cape? - Potts, Alistair (Department of Biological Sciences, 2023)
Late Pleistocene terrestrial climate information in the Western Cape. South Africa may be preserved in oxygen and carbon isotope ratios in paedogenic calcrete that bas Conned in zeuweltjies (large circular earth mounds). He11weltjles are common landscape features and their potential as palaeoclimatic archives is not known, simply because it has never been investigated. Samples were taken from three depth-profiles down a single hemvcltjie near Worcester. Carbon and oxygen isotope ratios were detennincd. In total, fifty-four samples were analysed. The o13C values vary from -7.4%. to -4.9%0 relative to PDB. whereas 15180 vary from 28.05'160 to 30.91%0 relative to SMOW.